PROBLEMA CIENTÍFICO DE INVESTIGACIÓN - Argota-Pérez, George (2019)
Although the scientific problem can be redefi ned, it is the most complex methodological structure to pose, since the correct identification of the variables must guarantee the delimitation of the research object, possible spent time, conceptualclarity about the area of research involved, immediacy of questions as guides to elucidate and the objective availability of resources involved. Likewise, it harbors the curiosity to transform some undesired effects that justify, unresolved causes.The approach of the scientifi c problem of investigation requires for its justification, originality, transcendence, level of update and relevance; in addition, the use of available intellectual tools. The present work has the purpose of describinga practical algorithm for the correct approach of the scientific research problem.